Hybrid Minimally Invasive Approach for Transvenous Lead Extraction: A Feasible Technique in High‐Risk Patients. (9th February 2017) - BONTEMPI, LUCA; VASSANELLI, FRANCESCA; CERINI, MANUEL; BISLERI, GIANLUIGI; REPOSSINI, ALBERTO; GIROLETTI, LAURA; INAMA, LORENZA; SALGHETTI, FRANCESCA; LIBERTO, DARIA; GIACOPELLI, DANIELE; RAWEH, ABDALLAH; MUNERETTO, CLAUDIO; et al.
Hybrid Approach for Lead Extraction: Introduction: Despite the overall safety, transvenous lead extraction (TLE) remains a challenging procedure with inherent risks, where surgery can still be required in elective cases. In this study, we report our experience with a minimally invasive "hybrid" approach, defined as a procedure performed by an electrophysiologist with the support of a cardiac surgeon in the same operative session. Methods and Results: We reported 12 cases of planned hybrid lead extraction; minithoracotomy and thoracoscopy were performed on 10 (83%) and 2 (17%) patients, respectively. A total of 25 leads out of 27 (median lead age 19 years) were successfully extracted with laser, mechanical or combined transvenous sheath. In 3 patients, the direct monitoring of vascular and myocardial integrity allowed for prompt treatment of potential vascular injury during the lead extraction maneuvers. Mean in‐hospital stay was 4 ± 2 days. There were no major intraoperative complications and no deaths occurred after 30 days' follow‐up. Conclusion: The hybrid approach, with minithoracotomy or thoracoscopy, is feasible and it might increase the safety in the most challenging TLE procedures: the minimally invasive surgical intervention allows for continuous monitoring of the critical cardiac structures and prompt treatment of potential complications.